2016
DOI: 10.17344/acsi.2016.2449
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid and Calcium Treatments Improves Wheat Vigor, Lipids and Phenolics Under High Salinity

Abstract: Seed vigor is a complex physiological trait required to ensure the rapid and uniform emergence of plants in the field under different environmental conditions. Therefore, salicylic acid (SA, 0.5 mM) and calcium (Ca 2+ , 50 mM) priming were used as exogenous growth enhancers to stimulate wheat (Triticum durum Desf. cv. Yelken) seed vigor under high salinity. The main aim was to address whether priming of wheat with SA, Ca 2+ and SA+Ca (SA, 0.5 mM + Ca 2+ , 50 mM; their combination) could bring about supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…This study verified that the CaCl 2 treatment could significantly induce elevation of protein expression and activity of PAL. It further led to high contents of total phenolic compounds and phenolic acids (Figs and ), consistent with previous studies . While, Ca 2+ channel blockers La 3+ and the Ca 2+ release channel inhibitor 2‐APB significantly hindered NaCl‐induced PAL activity and its gene expression.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This study verified that the CaCl 2 treatment could significantly induce elevation of protein expression and activity of PAL. It further led to high contents of total phenolic compounds and phenolic acids (Figs and ), consistent with previous studies . While, Ca 2+ channel blockers La 3+ and the Ca 2+ release channel inhibitor 2‐APB significantly hindered NaCl‐induced PAL activity and its gene expression.…”
Section: Discussionsupporting
confidence: 90%
“…It further led to high contents of total phenolic compounds and phenolic acids ( wileyonlinelibrary.com/jsfa and 5), consistent with previous studies. 8,9 While, Ca 2+ channel blockers La 3+ and the Ca 2+ release channel inhibitor 2-APB significantly hindered NaCl-induced PAL activity and its gene expression. In addition, reductions in phenolic compound content and PAL activity were also observed in response to Ca 2+ chelator EGTA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported positive effects on plant biomass under abiotic stress conditions after the application of SA, GA, SoA, MA, and LA, although none with respect to nutrient imbalance. Related to this, SA application at different concentrations, 0.5 mM (69 mg/L) in seeds of wheat [49], 100-300 mg/L sprayed in rosemary leaves [50] or 0.7-1.4 mM (96-193 mg/L) sprayed in sunflower [51] with high salinity showed a significant increase in FW. Applications in the nutrient solution of 1-2 mM (170-240 mg/L) GA in soybean under low temperatures [22] or applications of 0.75-1 mM (127-255 mg /L) GA in rice under salinity [20] increased the relative growth rate compared to the control.…”
Section: Discussionmentioning
confidence: 99%